Metodología para la determinación de los costos agropecuarios de la producción del tomate de riñon en la microempresa Agrodesiree S.A.S en período julio – octubre, año 2023. - Coque Benavides, Cinthya Piedad (2024)
The small enterprise dedicated to the production of agricultural products play a leading role in the economic and social development of Ecuador. Besides, this farmers are involved in agricultural activities, particularly the kidney tomato production, but the lack of knowledge of accounting management of their costs means that their permanence and stability in the market may be affected. In fact, the objective of the project is to determine the accounting treatment of biological assets in the microenterprise AGRODESIREES S.A.A in the period July - October 2023. In addition, is important mention that this investigation was apply a quantitative approach and field research which obtained directly from the investigated subjects, for describe the results. At the same time, the investigators used an interview technique to collect information provided by those responsible for the cultivation and harvest of the lot. Afterwards, the study was applied in the AGRODESIREE microenterprise in the city of Ambato. Last but not least, the results obtained when calculating the cost of production, with the information obtained from the agricultural accounting system applied to its different stages like: sowing, guidance, flowering, and production. Hence, identifying its real fair value per lot of $5,118.59 and per kilo that is $0.51, contributing positively to food, economy, and employability in the province of Tungurahua.